Molecular characterization of sub-frontal recurrent medulloblastomas reveals potential clinical relevance - Chen, Zirong; Yang, Huaitao; Wang, Jiajia; Long, Guoxian; Xi, Qingsong; Chen, Tao; He, Yue; Zhang, Bin; Wan, Feng (Frontiers in Neurology, 2023)
Background: Single recurrence in sub-frontal region after cerebellar medulloblastoma (MB) resection is rare and the underlying molecular characteristics have not been specifically addressed. Methods: We summarized 2 such cases in our center. All the 5 samples of them were molecularly profiled for their genome and transcriptome signatures. Results: The recurrent tumors displayed genomic and transcriptomic divergence. Pathway analysis of recurrent tumors showed functional convergence in metabolism, cancer, neuroactive ligand-receptor interaction, and PI3K-AKT signaling pathways. Notably, the sub-frontal recurrent tumors had a much higher proportion (50-86%) of acquired driver mutations than reported in other recurrent locations. The acquired putative driver genes in the sub-frontal recurrent tumors functionally enriched for chromatin remodeler associated genes, such as KDM6B, SPEN, CHD4, and CHD7. Furthermore, the germline mutations of our cases showed a significantly functional convergence in focal adhesion, cell adhesion molecules, and ECM-receptor interaction. Evolutionary analysis showed that the recurrence could be derived from a single primary tumor lineage or had an intermediate phylogenetic similarity to the matched primary one. Conclusion: Rare single sub-frontal recurrent MBs presented specific mutation signatures that might be related to the under-dose radiation. Particular attention should be paid to optimally covering the sub-frontal cribriform plate during post-operative radiotherapy targeting.